EKSTRAKURIKULER TAHFIDZ Al-QUR’AN SEBAGAI UPAYA PENANAMAN KARAKTER ISLAMI DI SMP MUHAMMADIYAH 1 SUKOHARJO - Amim Muslim; Dian Putri Ayuni; Mahadhika Wipradharma; Hagni Wijanti (Buletin Literasi Budaya Sekolah, 2021)
Tahfidz’s activities at SMP Muhammadiyah 1 Sukoharjo strive to shape Islami Character toward student. This study aims to (1) describe the Islamic character education of students with the Tahfidz extracurricular (2) describe the management efforts of the Tahfidz extracurricular in improving the Islamic Character of students. This type of research is descriptive qualitative, the subjects are students of SMP Muhammadiyah 1 Sukoharjo, while the object is the extracurricular activities of Tahfidz at SMP Muhammadiyah 1 Sukoharjo.  The result of this research is 1) to grow the order of Islamic Character at SMP Muhammadiyah 1 Sukoharjo which is carried out continuously and dynamically to form positive habits in student, 2) Effrorts to maintain Tahfidz extracurricular activities, the school tries to sceate a schedule that is able to be followed by students on an ongoing basis.